A Simple and Green Procedure for the One-Pot Synthesis of α-Aminophosphonates with Quaternary Ammonium Salts as Efficient and Recyclable Reaction Media - Yu, Ya-Qin; Xu, Da-Zhen (Synthesis, 2015)
A simple and highly efficient approach has been developed for a multicomponent one-pot reaction of aldehydes or ketones with amines and diethyl or triethyl phosphite to give the corresponding α-aminophosphonates. In the presence of quaternary ammonium salts, which are environmental friendly, inexpensive, and recyclable, α-aminophosphonates were obtained in excellent yields at room temperature within short times.
Keywords: aminophosphonates; multicomponent reactions; quaternary ammonium salts; green chemistry; phosphorylations